1991
DOI: 10.1128/mcb.11.9.4796-4803.1991
|View full text |Cite
|
Sign up to set email alerts
|

Multiple CArG Boxes in the Human Cardiac Actin Gene Promoter Required for Expression in Embryonic Cardiac Muscle Cells Developing In Vitro from Embryonal Carcinoma Cells

Abstract: Chimeric genes composed of the human cardiac actin promoter driving the Escherichia coli lacZ reporter gene were constructed, transfected, and stably integrated into genomes of P19 embryonal carcinoma cells. The transfected constructs were expressed actively in cardiac myocytes formed following dimethyl sulfoxide (DMSO)-induced cell differentiation but poorly in undifferentiated cultures and in cultures treated with retinoic acid to develop into derivatives of the neuroectoderm. A number of deletions of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…The /3-actin control probe detected an mRNA of approximately 2 kb in each lane. As previously reported, a smaller form of /3-actin mRNA was also present in heart and skeletal muscle (Lamballe et al, 1991;Pari et al, 1991). The murine and human HCII transcripts were both approximately 2.2-2.3 kb in length (Figure 7).…”
Section: Quantification Of Dermatan Sulfate Cofactor In Murinesupporting
confidence: 77%
“…The /3-actin control probe detected an mRNA of approximately 2 kb in each lane. As previously reported, a smaller form of /3-actin mRNA was also present in heart and skeletal muscle (Lamballe et al, 1991;Pari et al, 1991). The murine and human HCII transcripts were both approximately 2.2-2.3 kb in length (Figure 7).…”
Section: Quantification Of Dermatan Sulfate Cofactor In Murinesupporting
confidence: 77%
“…An alternative mechanism by which a gene could be expressed both in skeletal and in cardiac muscle is that a cardiac-specific factor could recognize and bind to the MyoD regulatory element. Analysis of the human cardiac a-actin promotor reveals that the sequences essential for expression in cardiac myocytes are similar to those implicated in MyoD-induced enhancement, suggesting that cardiac muscle might contain a MyoD-like activity (Pari et al, 1991). That two different factors could bind to the same consensus sequence has been observed for the basic helix-loop-helix (bHLH) family of transcriptional proteins (Weintraub et al, 1991).…”
Section: Discussionmentioning
confidence: 92%
“…The cells were selected in puromycin. The CA promoter is normally active only in muscle cells but is activated by MyoD in nonmuscle cells (37,49). Thus, only P19[MyoD] cells should contain active CA promoters and become puromycin resistant.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that expression of transcripts encoding MyoD did not induce myogenesis in P19 cells (37). In this study, we have examined how the ectopic expression of MyoD affects the developmental potential of P19 cells.…”
mentioning
confidence: 93%
See 1 more Smart Citation